Posterior Cruciate Ligament Injuries A Practical Guide to Management - Fanelli, MD, Gregory C. (Springer International Publishing : Imprint: Springer, 2015)
Now in a revised and expanded second edition including ten new chapters, this classic text on the diagnosis and management of posterior cruciate ligament injuries represents the state of the art. Comprehensive and used-friendly, the book covers PCL anatomy and biomechanics, diagnosis and evaluation, and both surgical and non-surgical treatment strategies. Surgical chapters discuss graft selection and open and arthroscopic techniques, including both primary and revision surgery and combined reconstruction with other knee ligaments. New chapters illustrate cutting-edge and advanced surgical techniques in reconstruction and primary repair, articular cartilage resurfacing and meniscus transplant in the PCL injured knee, mechanical graft tensioning, the role of osteotomy, treatment of PCL injuries in children, results of treatment and outcomes data in PCL injuries, clinical case studies, and the editor's experience chapter based on 24 years of treating PCL injuries. Complications, bracing and rehabilitation round out the presentation. Written and edited by leaders in the management of injuries to the knee, this will be an invaluable text for orthopedic surgeons and sports medicine practitioners alike.